PENGARUH KEPEMIMPINAN KEPALA DINAS PEREMPUAN TERHADAP BUDAYA KERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN DHARMASAYA - Fitria Wulandari; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The purpose of this study was to analyze how much influence the leadership of the female department head on the work culture of employees at the Environmental Service Office of Dharmasraya Regency, West Sumatra. This research uses quantitative methods. The sampling technique was done using purposive sampling. Quantitative data were collected using a Likert scale questionnaire that had been tested for validity and reliability. The total population of employees of the Environmental Service Office of Dharmasraya Regency is 62 people, with this study researching with a total sampling technique. The reason for this research is because there are very few women leaders in government institutions in Indonesia, especially in Dharmasraya Regency. In this study, it can be seen that there is a positive influence of the leadership of the female department head on the work culture of employees that have been tested with the T-test, and a small significance value of 0.00 is obtained from 0.05 and the percentage contribution of variable X to Y is 19.6%. The value stated in this study is that the better the leadership abilities, the better the employee's work culture.